2012
DOI: 10.1242/jcs.107474
|View full text |Cite
|
Sign up to set email alerts
|

Acentrosomal spindle organization renders cancer cells dependent on the kinesin HSET

Abstract: SummaryCentrosomes represent the major microtubule organizing centers (MTOCs) of animal somatic cells and orchestrate bipolar spindle assembly during mitotic cell division. In meiotic cells, the kinesin HSET compensates for the lack of centrosomes by focusing acentrosomal MTOCs into two spindle poles. By clustering multiple centrosomes into two spindle poles, HSET also mediates bipolar mitosis in cancer cells with supernumerary centrosomes. However, although dispensable in non-transformed human cells, the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 66 publications
(86 reference statements)
6
108
0
Order By: Relevance
“…Mouse oocytes contain acentriolar centrosomes (MTOCs) that fragment and cluster to form meiosis I spindle poles. The mechanism by which oocytes use these MTOCs to build spindles is of great interest because of the high frequency of aneuploidy in female gametes (Hassold and Hunt, 2001), and the similarities of this clustering mechanism to that found in some cancers (Breuer et al, 2010;Kleylein-Sohn et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse oocytes contain acentriolar centrosomes (MTOCs) that fragment and cluster to form meiosis I spindle poles. The mechanism by which oocytes use these MTOCs to build spindles is of great interest because of the high frequency of aneuploidy in female gametes (Hassold and Hunt, 2001), and the similarities of this clustering mechanism to that found in some cancers (Breuer et al, 2010;Kleylein-Sohn et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of HSET/KIFC1 in BT-549 cells caused not only centrosome declustering but also induced the formation of multipolar spindles with acentrosomal poles [147]. These observations demonstrate that HSET has a dual role in promoting bipolar spindle formation in cancer cells: promoting the clustering of extra centrosomes and the coalescence of acentrosomal poles that are aberrantly generated in BT-549 cells [147]. This study suggested that DNA damage signalling, which is commonly activated in cancer cells and is induced by many chemotherapeutic agents, contributes to the generation of acentrosomal spindle poles that need to be clustered to achieve a bipolar mitosis.…”
Section: Targeting Cells With Extra Centrosomes For Cancer Therapymentioning
confidence: 98%
“…E, immunoblotted extracts and NeutrAvidin pulldowns from cells synchronized as in D but released from prometaphase block for 15 min (metaphase, M*) or 30 min (C1 phase) were probed with anti-cyclin B1 antibody to reveal specific pulldown of ubiquitinated cyclin B1 from samples in which the SAC was inactivated. formation (52,53). During mitotic exit, KIFC1 has been shown to contribute to organization of the central spindle (54).…”
Section: Purification Of a Mitotic Exitmentioning
confidence: 99%